USE OF DYE IN THE PREOPERATIVE MARKING OF NONPALPABLE BREAST : LESIONS LITERATURE REVIEW - Eulálio Filho, Walberto Monteiro Neiva; Guimarães, Amanda Leal; Medeiros Neto, Antônio Marques de; Moura, Luana Araujo Borges de; Gomes, Carolina Gaze Gonçalves Fontenele; Vieira, Sabas Carlos (Mastology, 2019)
Objective: To evaluate and compare the use of different dyes in the marking of nonpalpable breast lesions indicated for surgical resection. Method: We analyzed the following variables: number of cases, types of dye, technique used for marking (patent blue, indocyanine green, or methylene blue), associated techniques (guidewire or Tc-99m), free margins of the surgical specimen (when the diagnosis was cancer), pain during the marking, and allergic events. The main results of the articles were organized in tables, using the software Microsoft Excel 2011. Results: We selected 11 articles for analysis. A total of 510 women had 516 nonpalpable breast lesions marked with dyes. The main dyes used were patent blue, methylene blue, and indocyanine green. The rate of free margins in cancer cases was 95%. Methylene blue was superior to other dyes in obtaining free margins. Out of the 11 articles selected, three associated dye with radioactive materials, and two with guidewire. Two studies analyzed the pain during the marking and revealed that 75% of the patients classified it as moderate or minimal, with mammography being the method most associated with pain. No allergic event was reported. Conclusion: The use of dyes in the preoperative marking of nonpalpable breast lesions is a viable, safe, and cheap technique. The initial results of several groups indicate significant advantages compared to the methods currently available. Methylene blue has a lower rate of positive margins than other dyes. Prospective randomized studies are still necessary to verify the superiority of the technique in comparison to others.